Changes in Black-White Difference in Lung Cancer Incidence among Young Adults. Issue 4 (20th August 2020) - Jemal, Ahmedin; Miller, Kimberly D; Sauer, Ann Goding; Bandi, Priti; Fidler-Benaoudia, Miranda M; Culp, MaryBeth; Islami, Farhad; Fedewa, Stacey A; Ma, Jiemin
Abstract: Background: We previously reported that lung cancer incidence between Blacks and Whites younger than 40 years of age converged in women and approached convergence in men. Whether this pattern has continued in contemporary young birth cohorts is unclear. Methods: We examined 5-year age-specific lung cancer incidence in Blacks and Whites younger than 55 years of age by sex and calculated the Black-to-White incidence rate ratios (IRRs) and smoking prevalence ratios by birth cohort using nationwide incidence data from 1997 to 2016 and smoking data from 1970 to 2016 from the National Health Interview Survey. Results: Five-year age-specific incidence decreased in successive Black and White men born since circa 1947 and women born since circa 1957, with the declines steeper in Blacks than Whites. Consequently, the Black-to-White IRRs became unity in men born 1967-1972 and reversed in women born since circa 1967. For example, the Black-to-White IRRs in ages 40-44 years born between 1957 and 1972 declined from 1.92 (95% confidence interval [CI] = 1.82 to 2.03) to 1.03 (95% CI = 0.93 to 1.13) in men and from 1.32 (95% CI = 1.24 to 1.40) to 0.71 (95% CI = 0.64 to 0.78) in women. Similarly, the historically higher sex-specific smoking prevalence in Blacks than Whites disappeared in men and reversed in women born since circa 1965. The exception to these patterns is that the incidence became higher in Black men than White men born circa 1977-1982. Conclusions: The historically higher lung cancer incidence in young Blacks than young Whites in the United States has disappeared in men and reversed in women, coinciding with smoking patterns, though incidence again became higher in Black men than White men born circa 1977-1982.